The Contestation of the Family Law Discourse in the Digital Age: Islam, State, and Gender - Ansori, Ansori; Juliansyahzen, Muhammad Iqbal (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This study examines the contestation of gender discourse in family law on social media and its relationship to religion and state law. This study seeks to answer three questions: how gender relations in the family are constructed on social media, how the struggle for the meaning of gender equality in family law occurs on social media, and why some digital activists in Indonesia have a dualistic understanding of religious law and state law in the context of family law. This is a qualitative study employing approaches from discourse analysis. Utilizing Bourdieu's theory, the researcher examines the contestation of gender relations discourse on social media. There are two groups with opposing viewpoints: those who oppose equality and those who support it. This study demonstrates that each gender narrative agent develops the discourse about the relationships between men and women using a variety of media, including YouTube, Instagram, Facebook, and an official website. Each has a large number of social media followers. There are numerous ways to disseminate discourse, including lectures, short videos, quotations, images, and scholarly articles. In the context of its relationship to state law, the first group tends to place the state in an overbearing role. This is understood due to the attitude of the state, which governs a number of matters not covered by the Shari'a. In contrast, the second group views religion and state law as mutually beneficial and therefore inseparable. There are a number of conclusions based on a variety of evidence, one of which is that religious authority in the media is fractured based on religious group affiliation, particularly in the family law debate. The problem of authority in the media is no longer defined by a character's scientific aptitude but by who has the most control over the media and the largest number of followers. In addition, sources of religious discourse, particularly family law, have shifted to a variety of media. In order to determine an authority's perspective in the media, it is vital to consider the fundamental values of Islam and perspectives that do not conflict with religion and the state.